The effect of relative pitch size on physiological, physical, technical and tactical variables in small-sided games: a literature review and practical guide - Rumpf, Michael C.; Jäger, Johannes; Clemente, Filipe M.; Altmann, Stefan; Lochmann, Matthias (Frontiers in Sports and Active Living, 2025)
IntroductionManipulating relative pitch size is a common practice in soccer training; however, published evidence on its true effects for practical coaching purposes has been lacking in the scientific literature. This review aimed to identify and quantify changes in physiological, physical, technical, and tactical variables resulting from increases in relative pitch size during small-sided games (SSGs) in soccer.MethodsA literature search was conducted, resulting in the inclusion of 56 articles in this review. Linear regression analysis was performed to examine the total and percentage changes in relative pitch size and its influence on physiological, physical, technical, and tactical variables collected during SSGs.ResultsLinear regression revealed that an increase in relative pitch size was significantly positively associated with higher values in lactate, RPE, and Edwards’ TRIMP (p < 0.05). No significant associations were found for heart rate metrics or player loads. Several physical variables showed significant positive associations (total distance, relative total distance, maximum speed, number of sprints, sprinting, high-speed running, jogging, acceleration and deceleration, high-metabolic load distance, work-to-rest ratio) and negative associations (walking distance) with increases in relative pitch size (p < 0.05). Larger relative pitch sizes were associated with a lower frequency of most technical actions (ball touches, dribbles, turnovers), while tactical variables showed significant positive associations (team width, surface area, stretch index, inter-team distance) and a negative association (spatial exploration distance) with changes in pitch size.ConclusionLarger relative pitch sizes can be implemented as a task constraint in SSGs to enhance physiological (e.g., lactate, RPE), physical (e.g., total distance, number of sprints), and tactical variables (e.g., surface area). Caution should be exercised regarding the potential negative impact on technical outcomes when increasing relative pitch size. Practitioners in soccer can utilize the findings of this review to achieve desired effects by adjusting relative pitch size to target specific training outcomes.